1984
DOI: 10.1093/oxfordjournals.aje.a113741
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin A, Carotene, Vitamin C and Risk of Lung Cancer in Hawaii

Abstract: The authors conducted a case-control study among the multiethnic population of Hawaii to test the hypotheses that lung cancer risk is inversely associated with dietary intake of total vitamin A, carotene, and vitamin C. Detailed dietary interviews were completed between September 1979 and October 1982 for 364 primary lung cancer patients and 627 general population controls matched on age and sex. After adjusting for a number of potentially confounding variables, including ethnicity, smoking history, and occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
3
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(63 citation statements)
references
References 0 publications
3
56
3
1
Order By: Relevance
“…Several carotenoids have been found to be protective against lung cancer in epidemiologic studies (52)(53)(54), though intervention trials using beta-carotene in heavy smokers (55,56) and physicians (57) have shown no benefit, and possible harmful effects. The variations among the ethnic groups in their intake of the different carotenoids might enable us to identify which, if any, of these constituents has a beneficial effect on lung cancer risk, and why intake of fruits and vegetables shows a consistent inverse association with the risk of this cancer (58).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Several carotenoids have been found to be protective against lung cancer in epidemiologic studies (52)(53)(54), though intervention trials using beta-carotene in heavy smokers (55,56) and physicians (57) have shown no benefit, and possible harmful effects. The variations among the ethnic groups in their intake of the different carotenoids might enable us to identify which, if any, of these constituents has a beneficial effect on lung cancer risk, and why intake of fruits and vegetables shows a consistent inverse association with the risk of this cancer (58).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Since then, there were many epidemiological studies [8][9][10][11][12][13][14] which have shown similar results such high dietary -carotene consumption from foods was a protective factor for certain types of cancer.…”
mentioning
confidence: 97%
“…In addition, folate supplementation has recently come under increased scrutiny given its effect on aggressive polyp formation in subjects at risk of colon cancer (23). Although there is information on possible mechanisms of these vitamins' effect on cancer (15,(24)(25)(26), epidemiologic studies in lung cancer have been mixed (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). A pooled analysis found no association with lung cancer and multivitamins, and total vitamin C, vitamin E, and folate, but had limited ability to detect an association with supplements (17).…”
mentioning
confidence: 99%